PELAKSANAAN PERJANJIAN PEKERJAAN JASA KONSTRUKSI PEMBUATAN LOKASI SUMUR EKSPLORASI ANUGERAH– 01 DAN PERBAIKAN JALAN MASUK LOKASI BLOK MARQUISA ANTARA PT. SCHINTAR MARQUISA DENGAN PT. SUKA DAMAI KONSTRUKSI DI PROVINSI RIAU - Rozi, Syafilla; Bachtiar, Maryati; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Construction services are one of the economic activities that have animportant role in achieving various targets to support the realization of nationaldevelopment goals. There are two parties in construction services who enter intoa legal employment relationship, namely the service user and the serviceprovider. The work relationship between service users and service providers isbased on law, and is stated in the form of a construction work contract. A contractcan be said to be an agreement because the contract contains a mutually bindingagreement and must be agreed to by both parties. During the implementation ofthe agreement, if one of the parties breaks their promise then that party can besaid to be in default or what could be called a breach of contract.The method for writing this research was carried out using sociologicallegal research. This research was conducted in Mandau District, BengkalisRegency, Riau Province because of data obtained from PT Suka DamaiConstruction. The author took samples including the Director of PT Suka DamaiConstruction Rokan Hulu, PT Schintar Marquisa staff, and legal counsel from PTSuka Damai Construction. The data sources in this research are primary andsecondary data with primary legal materials, secondary legal materials andtertiary legal materials. The data obtained was collected through interviews andliterature review.Based on the results of research on the problem, there are two main thingsthat will be concluded. Settlement of default on Cooperation Agreement by PT.Suka Damai Construction with PT. Schintar Marquisa began with a cooperationagreement between PT. However, various efforts made by the defaulting partiesremain unresolved. Suggestions for firmness from PT. Suka Damai Constructionand, if necessary, take legal action, both non-litigation and litigation, to resolvethe breach of contract issue.Keywords: Construction Services, Contracts, Agreements, Default.